Energy justice and offshore oil: weighing environmental risk and privilege in the North Atlantic. Issue 4 (1st October 2020) - Stoddart, Mark C.J.; Burt, B. Quinn
ABSTRACT: We examine framing of the social-ecological benefits and risks of offshore oil development across the North Atlantic region (Denmark, Newfoundland and Labrador, Norway, and Scotland). Drawing on field observation and interviews, we show that the environmental privileges of the oil sector are legitimated through frames that emphasize economic contributions to social wellbeing, as well as through frames of maintaining global competitiveness for host societies. There is generally a high level of trust in existing systems of oil governance to ensure responsible resource extraction. Where environmental risk framing emerges, this focuses on local impacts of new oil development that disproportionately impacts rural coastal communities that depend on tourism and fisheries. Environmental risk framing also relates to issues of decommissioning and global climate change. Throughout our analysis, we attend to differences in framing across our case study regions. We show that energy justice research benefits from greater engagement with two distinct, but related aspects of analysis: 1) environmental privilege and environmental risk; and 2) localised and globalised environmental risk.